Effect of Organic Fertilizer on Growth and Productivity of Ipomoea reptans Poir - Klementinus Bhato; Yohanes Bare; Oktavius Yoseph Tuta Mago (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Kangkung Darat (Ipomoea reptans Poir) is the vegetable that is popular and consumed by the community. Chemical fertilizers bring negative impacts on soil and consumer health, lead to change thewith liquid organic fertilizer from cattle dung and tofu industrial waste with floating raft hydroponic planting techniques. The purpose of this study was to analyze the effect of liquid organic fertilizer on the growth and productivity of Ipomoea reptans Poir. The research was conducted on the campus of the University of Nusa Nipa Indonesia. The research method, quantitative data collection using a Randomized Block Design (RAK) consisting of 5 treatments, namely P0 = 0% (control), P1 = 20%, P2 = 40%, P3 = 60%, P4 = 80%. Parameters observed were plant height, number of leaves and wet weight. The data obtained were analyzed using SPSS version 16.0 with an advanced test, namely the DMRT (Duncan's Mutiple Range Test) test. The results showed that the application of liquid organic fertilizer from cow dung and tofu industrial waste had a significant effect on the growth and productivity of Ipomoea reptans Poir. The effects include the growth of plant height and number of leaves as well as the yield of Ipomoea reptans Poir including wet weight (fresh) with the best concentration of P2 treatment with 40% POC concentration This research provides benefits for the community, especially the potential as farmers to further motivate the use of liquid organic fertilizer made from cow dung and tofu waste to increase crop income and soil fertility.